2006
DOI: 10.1088/0953-8984/18/28/001
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a non-local interfacial Hamiltonian for short-ranged wetting: I. Double-parabola approximation

Abstract: We derive a non-local effective interfacial Hamiltonian model for short-ranged wetting phenomena using a Green's function method. The Hamiltonian is characterized by a binding potential functional and is accurate to exponentially small order in the radii of curvature of the interface and the bounding wall. The functional has an elegant diagrammatic representation in terms of planar graphs which represent different classes of tube-like fluctuations connecting the interface and wall. For the particular cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
124
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(132 citation statements)
references
References 37 publications
(78 reference statements)
8
124
0
Order By: Relevance
“…From layer to layer, the dependence on the film thickness is given by the same exponential decay, ∼e −λξ IS , as the potential (ξ IS ), where the decay constant λ is the inverse correlation length in the bulk liquid. The dependence on q fits well into the form (ξ IS ) + q 2 γ w (0)e −λξ IS used in the RG analysis by Fisher and Jin, 3 but the nonlocal effects pointed out by Parry et al 4,5 appear to be strong and clear in the contribution γ LV (q), independent of ξ IS , which gives the free liquid surface limit for thick films. In this respect, our method to extract the CW fluctuations from the molecular positions gives a quantitative and testable link between the molecular and the mesoscopic descriptions of wetting films.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…From layer to layer, the dependence on the film thickness is given by the same exponential decay, ∼e −λξ IS , as the potential (ξ IS ), where the decay constant λ is the inverse correlation length in the bulk liquid. The dependence on q fits well into the form (ξ IS ) + q 2 γ w (0)e −λξ IS used in the RG analysis by Fisher and Jin, 3 but the nonlocal effects pointed out by Parry et al 4,5 appear to be strong and clear in the contribution γ LV (q), independent of ξ IS , which gives the free liquid surface limit for thick films. In this respect, our method to extract the CW fluctuations from the molecular positions gives a quantitative and testable link between the molecular and the mesoscopic descriptions of wetting films.…”
Section: Discussionsupporting
confidence: 66%
“…3(b) and the theoretical framework suggests that the enhanced (or subdamped) CW fluctuations that create the oscillatory behavior of γ (q,ξ IS ) could be spurious or irrelevant in the RG flux. The present procedure may also be applied to the study of wetting layers on structured substrates where nonlocal effects could be more relevant to contrast with the predictions of Fisher and Jin 3 and Parry et al 4,5 Work addressing these questions is in progress and will be reported in the future.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Progress has recently been made towards resolving problems in the theory of three-dimensional (3D) shortranged wetting [1-3] from analysis of a nonlocal (NL) interfacial Hamiltonian [4 -6]. Starting from a LandauGinzburg-Wilson (LGW) model, it can be shown that the interfacial binding potential contains two-body interfacial interactions and also has a simple diagrammatic representation [5,6]. The latter allows one to visualize the binding potential as arising from tubelike fluctuations that zigzag between the surfaces.…”
mentioning
confidence: 99%